Synthesis and Characterization of Lead(II), Bismuth (III), Titanium(IV), Selenium(IV), Thorium(IV), Dioxomolybdenum (VI) and Dioxouranium(VI) Hexamethyleniminecarbodithioate and their Biological Activities. - BHAT, G.S.; SAWANT, A.D. (Asian Journal of Chemistry, 2010)
The lead(II), bismuth(III), titanium(IV), selenium(IV), thorium(IV), dioxomolybdenum(VI) and dioxouranium(VI) hexamethyleniminecarbodithioate complexes of the type M(HMICdt)2, M(HMICdt)3, M(HMICdt)4, MO2(HMICdt)2 (where M = Metal and HMICdt = Hexamethyleniminecarbodithioate) have been synthesized and characterized by elemental analysis, molar conductance, magnetic measurements,electronic, IR, 1H NMR spectroscopy. The dithio ligand exhibit univalent bidentate character and coordinates with metal symmetrically through bisulfur fork. All these complexes have been tested for their activity against bacteria and fungi and found to possess both antibacterial and antifungal activities.